2022
DOI: 10.1186/s12870-022-03762-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of transcriptome and metabolome reveals flavonoid biosynthesis regulation in Rhododendron pulchrum petals

Abstract: Background Color is the major ornamental feature of the Rhododendron genus, and it is related to the contents of flavonoid in petals. However, the regulatory mechanism of flavonoid biosynthesis in Rhododendron pulchrum remains unknown. The transcriptome and metabolome analysis of Rhododendron pulchrum with white, pink and purple color in this study aimed to reveal the mechanism of flavonoid biosynthesis and to provide insight for improving the petal color. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 90 publications
3
15
0
Order By: Relevance
“…F3'5'H (evm.TU.contig31.16) catalyzes the synthesis of dihydromyricetin, a substrate of leucodelphinidin. These results are consistent with those of similar studies of Rhododendron pulchrums (Xia et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…F3'5'H (evm.TU.contig31.16) catalyzes the synthesis of dihydromyricetin, a substrate of leucodelphinidin. These results are consistent with those of similar studies of Rhododendron pulchrums (Xia et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…L-phenylalanine is converted to cinnamic acid by PAL, the frist enzyme in the flavonoid biosynthetic pathway (Heldt and Piechulla, 2011). In addition to PAL, C4H, CHS, and 4CL play critical roles in the synthesis of crucial secondary metabolites such as lignin, phenolic acids, coumarin, flavonoids, and anthocyanins (Chen et al, 2022;Xia et al, 2022). Subsequently, r-Coumaric-CoA produces naringenin, which is catalyzed by CHS and CHI (Yuan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol and quercetin both belong to flavonols and play key roles in plant color formation (Chen et al., 2021; Miyahara et al., 2016; Yoshida et al., 2021). By controlling the synthesis of key enzymes, plants regulate the types and contents of flavonoid metabolites and thus control the formation of flower color (Wang, Ren, et al., 2021; Xia et al., 2022; Yang et al., 2021). Studies have shown that flavonoids are important factors for color formation in Acer truncatum , apple ( Malus × domestica ), and sweet potato ( Ipomoea batatas ) (El‐Sharkawy et al., 2015; Qiao et al., 2022; Zhao et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The potent Trichoderma was employed mycoparasitism as a biocontrol action to restrain fungal pathogen (Hirpara & Gajera, 2020), and providing an environmentally sound alternative to chemical fungicides in the management of different pathogens. “Omics” technologies, including metabolomics and transcriptomics might be provided information on the global profile, and are therefore regarded as powerful tools to investigate molecular mechanisms of various traits for crop improvement and protection (Guo et al, 2022; Xia et al, 2022). The miRNAs interfering with the regulation of genes and pathways are not clearly explored to understand molecular mechanisms in agriculturally beneficial fungi.…”
Section: Introductionmentioning
confidence: 99%
“…"Omics" technologies, including metabolomics and transcriptomics might be provided information on the global profile, and are therefore regarded as powerful tools to investigate molecular mechanisms of various traits for crop improvement and protection (Guo et al, 2022;Xia et al, 2022). The miRNAs interfering with the regulation of genes and pathways are not clearly explored to understand molecular mechanisms in agriculturally beneficial fungi.…”
mentioning
confidence: 99%